Ordinary angels [videorecording (DVD)] - Tilly, Meg; Fremon, Kelly; Swank, Hilary; Ritchson, Alan, 1984-; Travis, Nancy, 1961-; Jones, Tamala; Powell, Drew, 1976-; Acker, Amy, 1976-; Hughes, Skywalker; Mitchell, Emily (Actress); Burgos-Goizueta, Pancho; Bankovic, Maya (Lionsgate, 2024)
Based on a remarkable true story, ORDINARY ANGELS centers on Sharon Steves, a fierce but struggling hairdresser in small-town Kentucky who discovers a renewed sense of purpose when she meets Ed Schmitt, a widower working hard to make ends meet for his two daughters. With his youngest daughter waiting for a liver transplant, Sharon sets her mind to helping the family and will move mountains to do it. What unfolds is the inspiring tale of faith, everyday miracles, and ordinary angels.